Micropropagation of Sicilian cultivars with an aim to preserve genetic diversity in hazelnut (Corylus avellana L.). (3rd September 2019) - Sgueglia, A.; Gentile, A.; Frattarelli, A.; Urbinati, G.; Germanà, M. A.; Caboni, E.
Abstract: The use of a small number of cultivars in agriculture can lead to a loss of agrobiodiversity. Since i n vitro techniques are valuable tools for conserving plant biodiversity, an efficient micropropagation protocol for four Italian hazelnut cultivars, 'Carrello', 'Ghirara', 'Minnulara', and 'Panottara', was developed. The highest axillary bud survival was obtained after decontamination with 40 min 1% sodium hypochlorite followed by 40 min 0.1% sodium merthiolate in 'Minnulara' and 'Ghirara', while the 35 + 35 min treatment was the best for 'Carrello' and 'Panottara'. Shoot multiplication was higher in 'Minnulara' and 'Ghirara' when 6.6 μM N 6 -benzyladenine was used, even if some hyperhydric shoots were observed, while metatopolin was more effective in the other two cultivars. In vitro rooting, performed in 'Carrello' and 'Panottara', was higher with 17.6 than with 9.8 µM indole-3-butyric. Following in vitro root induction with 17.6 µM indole-3-butyric acid for 7 days, rooting and acclimatisation in greenhouse exceeded 85% for all four cultivars.